Consumption of a drink containing extruded sorghum reduces glycaemic response of the subsequent meal - Anunciação, Pamella Cristine; Cardoso, Leandro de Morais; Queiroz, Valéria Aparecida Vieira; de Menezes, Cicero Beserra; de Carvalho, Carlos Wanderlei Piler; Pinheiro-Sant’Ana, Helena Maria; Alfenas, Rita de Cássia Gonçalves (European journal of nutrition, 2018)
Purpose Glycaemic control is essential to prevent the manifestation of diabetes in predisposed individuals and the development of associated comorbidities. It is believed that sorghum may modulate the glucose response. In this study, we investigated the effect of extruded sorghum consumption, and the profile of bioactive compounds, on postprandial glycaemia of a subsequent meal in normal weight and normoglycaemic subjects. Methods This was a randomized, single-blind, crossover designed study. After a 12 h overnight fasting, ten subjects reported to the laboratory to participate in four experimental sessions, and consumed one of three sorghum test drinks: sorghum P 3-DXAs (with proanthocyanidins—P and rich in 3-deoxyanthocyanidins—3-DXAs); 3-DXAs (without proanthocyanidins and rich in 3-DXAs); and control (low in 3-DXAs and without proanthocyanidins); or a non-sorghum drink. 30 min later, the subjects consumed a glucose solution (25 g glucose). Glycaemic response was monitored at times 0 (before glucose solution), 15, 30, 45, 60, 90, 120 min (after glucose solution consumption). The incremental areas under the glycaemic curve (iAUC) were calculated by the trapezoidal method. Results Intake of P 3-DXAs drink before the glucose solution resulted in a postprandial iAUC lower than the other sorghum test drinks. Sorghum drinks minimized the postprandial glycaemia peak. Conclusion Sorghum drinks consumption, especially the P 3-DXAs drink, 30 min before the glucose solution resulted in lower iAUC compared to the non-sorghum drink, leading to a lower glycaemic response.